Xeroderma Pigmentosum with Squamous Cell Carcinoma: A Case Report and Literature Review - Moniruzzaman, ASM; Absar, MN; Sarker, Shamsuzzaman; Sarker, Mahmudul Haque; Sattar, Md Abdus; Shaha, Chandan Kumar; Basak, Atanu Kumar; Khairuzzaman, Md (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v30i1.6189 Bangladesh J Child Health 2005; Vol 29 (3): 104-106